2015
DOI: 10.1111/jfpp.12666
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Arrhenius Model and the Radial Basis Function Neural Network (RBFNN) Model to Predict Quality of Thawed Shrimp (S olenocera melantho ) Stored at Different Temperatures

Abstract: Changes in quality of thawed shrimp (Solenocera melantho) stored at −3, 0, 3 and 6C were determined and modeled by the Arrhenius and the radial basis function neural network (RBFNN) models, based on total volatile base nitrogen , total aerobic counts, K value, hypoxanthine, pH, electrical conductivity (EC) and sensory assessment. A significant inhibition of spoilage was found in shrimp stored at −3C compared to those stored at 0, 3 and 6C. The prediction accuracy of the Arrhenius model was satisfactory for ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…With extended storage time, the K-value increased significantly (P < 0.05), but it increased faster after 56 days. Moreover, the K-values of shrimp stored at higher temperatures increased more quickly, which was consistent with the conclusion of Xu et al [21] That is, lower temperatures can slow down the autolysis rate of shrimp and inhibit the activity of 5'-nucleotidase, and the slower speed in ATP degradation can lead to a lower increasing rate of K-value. [29] Hx The process of ATP degradation in shrimp is as follows: ATP → ADP → AMP → IMP → HxR → Hx.…”
Section: K-valuesupporting
confidence: 89%
“…With extended storage time, the K-value increased significantly (P < 0.05), but it increased faster after 56 days. Moreover, the K-values of shrimp stored at higher temperatures increased more quickly, which was consistent with the conclusion of Xu et al [21] That is, lower temperatures can slow down the autolysis rate of shrimp and inhibit the activity of 5'-nucleotidase, and the slower speed in ATP degradation can lead to a lower increasing rate of K-value. [29] Hx The process of ATP degradation in shrimp is as follows: ATP → ADP → AMP → IMP → HxR → Hx.…”
Section: K-valuesupporting
confidence: 89%
“…[9][10][11] Radial basis function neural network (RBFNN) is a feed-forward neural network and has been proved to have a nearly perfect predictive accuracy. [12] RBFNN can develop a meaningful relationship between inputs and outputs through a learning process and obtain accurate predictive results by mimicking the real neural activity in the human brain. [13] Several previous studies have reported the benefits of using RBFNN model for quality prediction of aquatic products.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Several previous studies have reported the benefits of using RBFNN model for quality prediction of aquatic products. Xu et al [12] used the RBFNN model for predicting the quality of thawed shrimp stored at different temperatures (−3, 0, 3, and 6°C) and reported the accurate prediction. Wang et al [13] and Kong et al [14] applied RBFNN model to predict the quality changes of bream and common carp fillets during storage.…”
Section: Introductionmentioning
confidence: 99%
“…However, PLSR model may not consider the nonlinear relationships between protein oxidation and denaturation parameters and texture and moisture loss, and this deficiency could be compensated by radial basis function neural network (RBFNN) model. RBFNN can establish nonlinear function between input data and output data with a nearly perfect predictive accuracy during the fit-ting process (Xu et al, 2016). Shi et al (2017) used RBFNN model to predict the quality changes of frozen mud shrimp and obtained satisfactory predicting results.…”
Section: Introductionmentioning
confidence: 99%